2021
DOI: 10.1155/2021/6612456
|View full text |Cite
|
Sign up to set email alerts
|

Sexism-Related Stigma Affects Pain Perception

Abstract: People with stigmatized characteristics tend to be devalued by others in a given society. The negative experiences related to stigma cause individuals to struggle as they would if they were in physical pain and bring various negative outcomes in the way that physical pain does. However, it is unclear whether stigma related to one’s identity would affect their perception of physical pain. To address this issue, using sexism-related paradigms, we found that females had reduced pain threshold/tolerance in the Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Previous studies have shown that one experiences an increase in physical pain perception after experiencing social pain. 18 , 19 Consistent with these findings, we also found that social pain had a facilitatory effect when individuals suffer jointly from both physical and social pain. Photographs of ex-partners can be used to arouse negative emotions in individuals due to their past experiences of feeling hurt.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have shown that one experiences an increase in physical pain perception after experiencing social pain. 18 , 19 Consistent with these findings, we also found that social pain had a facilitatory effect when individuals suffer jointly from both physical and social pain. Photographs of ex-partners can be used to arouse negative emotions in individuals due to their past experiences of feeling hurt.…”
Section: Discussionsupporting
confidence: 87%
“…The ERP component (N1) was associated with pain perception caused by gender discrimination (Zhang et al, 2021). Participants in the pain empathy group exhibited increased discomfort and sensitivity when seeing others suffering pain, with a significant increase in the N1 amplitude (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] Cultural meanings of pain connected to female bodily functions may influence healthcare professionals and the affected women's perceptions and actions in their respective roles. 31 Feminist theory of the body argues that the male body is considered as normal and good, while specific female attributes that differentiate women from men are considered as inferior. 32,33 It follows that female bodily functions such as menstruation, pregnancy, abortion, childbirth and lactation become symbols of female inferiority and lead to devaluation.…”
Section: Dovepressmentioning
confidence: 99%